Catching leaders' mood: Contagion effects in teams - Judith Volmer (Administrative Sciences, 2012)
Much of the behavior at work takes place within teams. Leaders of teams experience different feelings that, in turn, can have an impact on how team members feel and perform. This study examined the effects of leaders' mood on individual team members' mood, group affective tone, and team outcomes (actual team performance, potency, and goal commitment) in a laboratory study, with a sample of 63 students working in three-person teams. Furthermore, the study investigated the mediating role of group affective tone in the leaders' mood-team outcomes relationship. Results demonstrated that leaders influence team members' individual mood, group affective tone, actual team performance, and potency. Moreover, group affective tone mediated the relationship between team leaders' mood and potency. Taken together, the findings suggest that in order to enhance subordinates' work experience and to attain desired outcomes, leaders should be aware of their mood and its potential effects.
Keywords: 350; leadership; mood contagion; group affective tone; potency; goal commitment; actual team performance; auditory mood induction